2012
DOI: 10.4067/s0718-58392012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Deficit on Iron and Zinc Uptake by Matricaria chamomilla L.

Abstract: Iron and zinc deficiency are a yield-limiting factor with major implications for field crop production in many agricultural regions of the world; this production is essential source of Fe and Zn in human and animal diets. Two experiments were conducted under greenhouse conditions to evaluate Fe and Zn uptake by German chamomile (Matricaria chamomilla L.) grown under several drought conditions. Treatments were arranged in four irrigation regimes (95%, 80%, 65%, and 50% field capacity) and six irrigation disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A few years ago the statement was made that “there are already publications dealing with total element concentrations in medicinal plants, but only a few investigations deal with more detailed information on the forms of these elements, for example, availability of metals by using different extractants, or correlation of extracted metals with total amounts of organic substances” [ 169 ]. While separate data usually exist for a certain herbal product regarding its iron and polyphenolic or tannin contents, they in most cases come from different studies; therefore, little is known about the potential correlations between the two and it is difficult to appreciate the real levels of the two in the same sample, as they rarely have been assessed in the same samples (to allow for firm conclusions).…”
Section: Discussionmentioning
confidence: 99%
“…A few years ago the statement was made that “there are already publications dealing with total element concentrations in medicinal plants, but only a few investigations deal with more detailed information on the forms of these elements, for example, availability of metals by using different extractants, or correlation of extracted metals with total amounts of organic substances” [ 169 ]. While separate data usually exist for a certain herbal product regarding its iron and polyphenolic or tannin contents, they in most cases come from different studies; therefore, little is known about the potential correlations between the two and it is difficult to appreciate the real levels of the two in the same sample, as they rarely have been assessed in the same samples (to allow for firm conclusions).…”
Section: Discussionmentioning
confidence: 99%
“…Sarajuoghı et al (2014) observed the highest Fe content of T. vulgaris under stress applied at 80% of the field capacity. However, Pirzad et al (2012) reported that water stress levels of 95%, 80%, 65% and 50% did not have a statistically significant effect on the amounts of Fe and Zn taken up by Matricaria chamomilla L. plants, but that severe stress conditions reduced the amounts of Fe and Zn taken up. On the contrary, it has been reported that in Hypnum cupressiforme (hypnum moss) (Sardans and Peñuelas, 2008) and maize (İbrahim et al, 2020), water stress significantly supressed Fe take-up, and thus reduced the plants' Fe contents.…”
Section: Manganese (Mn)mentioning
confidence: 94%